Evaluation of Anthrax Morbidity Rate in 2012, Prognosis for 2013 - E. I. Eremenko; A. G. Ryazanova; N. P. Buravtseva; O. I. Tsygankova; L. Yu. Aksenova; S. N. Antyuganov; E. A. Tsygankova; T. M. Golovinskaya; V. V. Voropaev; A. N. Kulichenko (Проблемы особо опасных инфекций, 2013)
Evaluated are epidemiological and epizootiological situations on anthrax in the Russian Federation and around the world in 2012. Displayed is the morbidity rate prognosis for 2013.